IMPROVEMENT OF PRESSURE AND COMPRESSIVE STRAIN SENSING USING PRISTINE CARBON NANOTUBES FOREST. - ,, MUHAMMAD YASAR (2016)
Carbon nanotubes (CNTs) are sought after as the alternative pressure and strainsensing element, as they have better electromechanical properties that persist to be predictable even at higher temperatures. Fundamental characteristics of the conventional semiconductor or metal based pressure/strain sensors limits their operation temperature to less than 100°C. Therefore the development of CNTs arrays as pressure sensing element would require the synthesis of the pristine, vertically aligned CNTs arrays with specific properties. Vertically aligned multi-walled carbon nanotubes (MWCNTs) arrays were synthesized via floating catalyst chemical vapor deposition (FCCVD) technique. Certain parameters of FCCVD method were optimized in order to grow millimeter long, aligned and mechanically resilient CNTs forest. Morphology of the synthesized MWCNTs arrays/forest were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM).